Republic of Chad : Shaping Adaptive Safety Nets to Address Vulnerability - World Bank (World Bank, Washington, DC, 2016)
This report is the result of extensive analytical work on social protection in Chad. During 2014 and 2015, the World Bank’s Social Protection and Labor (SPL) Global Practice undertook extensive analytical work in Chad to assess the country’s poverty and vulnerability profile, and the characteristics of its social safety nets system. This report, Republic of Chad – Shaping Adaptive Safety Nets to Address Vulnerability, is the result of such work and was prepared in the context of the renewed relationship between the Government of Chad and the World Bank. Such partnership includes the reengagement of the World Bank on the SPL agenda, and programming of World Bank support to Chad as part of the Systematic Country Diagnostic and the Country Partnership Framework.